UMUR PERUSAHAAN, UKURAN PERUSAHAAN, KEPEMILIKAN SAHAM PUBLIK DAN KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN - KHAIRUDIN KHAIRUDIN; AMINAH AMINAH; ANGGITA ANGGITA (Jurnal Akuntansi dan Keuangan, 2018)
This study aims to prove empirically the influence of company age, company size and ownership of the public on the completeness of the disclosure of financial statements. This research was conducted at the company LQ45 which listed on Indonesia stock Exchange in 2016. Company age is the first issue on the stock exchange up to the time of the study; the size of the company measured by the logarithm of total asset; ownership of the public shares is determined based on the ratio of the percentage of shares held by public shares to total shares; the completeness of the disclosure are expressed in the form of The Completeness of the Disclosure (the disclosure). Testing is performed with the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination. The research shows that company age and company size have no effect on the completeness of the disclosure of financial statements, while the public share ownership has positive and significant effect on the completeness of the disclosure of financial statements.Keywords: Company Age, Company Size, Public Ownership of the Shares and the Completeness of the Disclosure of Financial Statements.